Treatment-Emergent Neuroendocrine Prostate Cancer: A Clinicopathological and Immunohistochemical Analysis of 94 Cases - Zhang, Qingfu; Han, Yunan; Zhang, Yao; Liu, Dan; Ming, Jian; Huang, Bo; Qiu, Xueshan (Frontiers in Oncology, 2021)
Purpose This study aimed to evaluate the pathological characteristics, immunophenotype, and prognosis of treatment-emergent neuroendocrine prostate cancer (T-NEPC). Materials and Methods We collected 231 repeated biopsy specimens of castration-resistant prostate cancer (CRPC) cases between 2008 and 2019. We used histopathological and immunohistochemical evaluations of Synaptophysin (SYN), ChromograninA (CgA), CD56, androgen receptor (AR), and prostate-specific antigen (PSA) to screen out T-NEPC cases. Multivariate analyses were performed to identify factors in the prognosis of T-NEPC. Further, the results were verified in the Surveillance, Epidemiology, and End Results (SEER) program. Results Among the 231 CRPC cases, 94 (40.7%) cases were T-NEPC. T-NEPC were more likely to present with negative immunohistochemistry for AR (30.9%) and PSA (47.9%) than that of CRPC (8.8% and 17.5%, respectively). Kaplan-Meier analysis revealed that patients with T-NEPC (median overall survival [OS]: 17.6 months, 95% CI: 15.3–19.9 months) had significantly worse survival compared with usual CRPC patients (median OS: 23.6 months, 95% CI: 21.3-25.9 months, log-rank P = 0.001), especially in metastasis cases (median OS: 15.7 months, 95% CI: 13.3-18.0 months) and patients with small cell carcinoma component (median OS: 9.7 months, 95% CI: 8.2–11.2 months). Prostate adenocarcinoma with diffuse NE differentiation (median OS: 18.8 months, 95% CI: 15.3–22.3 months) had poor outcome than those with usual CRPC (P = 0.027), while there was no significant change in the focal NE differentiation (median OS: 22.9 months, 95% CI: 18.1–27.7 months, P = 0.136). In the unadjusted model, an excess risk of overall death was observed in T-NEPC with PSA negative (HR = 2.86, 95% CI = 1.39–6.73). Among 476 NEPC cases in the SEER database from 2004 to 2017, we observed a higher hazard of overall death in patients aged 65 years and older (HR = 1.35, 95% CI = 1.08–1.69), patients with PSA ≤ 2.5 ng/ml (HR = 1.90, 95%CI = 1.44–2.52), patients with PSA 2.6–4.0 ng/ml (HR = 2.03, 95%CI = 1.38–2.99), stage IV tumor (HR = 2.13, 95%CI = 1.47–3.08) and other races (HR = 1.85, 95%CI = 1.17–2.94) in total NEPC, adjusting for confounders. Similar hazard ratios were observed in pure NEPC, while there was no significant results among prostate adenocarcinoma with NE differentiation tumors. Conclusion T-NEPC was associated with an unfavorable prognosis, negative immunohistochemistry for PSA in T-NEPC and serum PSA level ≤ 4 ng/ml had a worse prognosis. Urologists and pathologists should recognize the importance of the second biopsy in CRPC to avoid unnecessary diagnosis and treatment delays.